Comprehensive analysis of Australia’s aged care system to inform policies for a sustainable future - Alsaeed, Turki; Washington, Tracy; Xia, Bo (Frontiers in Public Health, 2025)
BackgroundAustralia’s aging population presents significant socioeconomic challenges, necessitating the aged care sector reforms. Projections indicate continued growth in this demographic, prompting the implementation of various funding mechanisms to support healthy aging. However, notable disparities persist, including care quality concerns, workforce shortages, and safety issues, hindering the sector’s ability to meet consumer expectations. Despite recognition of these challenges, no comprehensive overview exists addressing these shortcomings. This study aims to provide a comprehensive analysis of the literature to identify these challenges and inform policy development.MethodsIn this study, a scoping review was conducted, examining primary and secondary sources, including peer-reviewed articles, government reports, and aged care policies. The Scopus database was searched using relevant keywords, and a snowball search technique was employed to identify additional literature. The inclusion criteria were applied, and journal articles were screened for titles and abstracts before full-text analysis. Thematic analysis was conducted on selected literature, and secondary data were from administrative and organizational websites and agencies.ResultsFindings indicate a preference for home-based care among older Australians due to concerns about quality and safety in aged care facilities. While the Australian government has developed reforms and policies to govern the sector, funding remains insufficient to meet the escalating demand for high-quality care. Challenges include workforce shortages, the growing burden of aging, and difficulties in adopting emerging technologies, which impact the quality of care delivered to older Australians.ConclusionThis paper serves as a resource for policymakers and aged care professionals, informing the development of reforms to address pressing issues in the sector. A comprehensive evaluation of existing knowledge provides a clearer understanding of current and future obstacles ensuring a holistic view and fostering the development of sustainable aged care reforms.